Couple's Bond: An Emotional Possibility to Grow - Juan Ortega-Rojas (Universidad Nacional, Costa Rica, 2012)
The bond between a couple is one of the most important ties developed in people's life.  Its significance implies examining our personal beliefs on that concept and being open to learn and adopt certain attitudes on different aspects in the relationship, such as: i) accepting the other person the way he or she is, as long as his/her character do not damage the other person's dignity, ii) constant communication, especially in times of crisis, iii) understanding and valuing oneself to understand and value the other person, iv) being thoughtful to please the other person, v) complying with commitments made and vi) trying new experiences by changing roles as one of the strategies. These aspects become recommendations which appropriately undertaken will facilitate the creation of healthier and longer lasting bonds.  In this context, this paper aims at encouraging the examination of your own behavior and ideas, in terms of couple's bond.  Taking some time to develop different attitudes seems to be the way to achieve a pleasant bond within an environment of mutual growth.